Most Important Things and Associated Factors With Prioritizing Daily Life in Patients With Advanced Lung Cancer. Issue 12 (8th December 2022) - Kameyama, Naofumi; Sato, Takashi; Arai, Daisuke; Fujisawa, Daisuke; Takeuchi, Mari; Nakachi, Ichiro; Kawada, Ichiro; Yasuda, Hiroyuki; Ikemura, Shinnosuke; Terai, Hideki; Nukaga, Shigenari; Nakano, Yasushi; et al.
Abstract : PURPOSE: Patients' values and priorities in their lives should be appreciated from an early phase of incurable diseases such as advanced cancer. However, studies examining these characteristics have been lacking. This study attempted to determine what patients with advanced lung cancer valued most, once they had been diagnosed, and any associated factors. METHODS: Patients with newly diagnosed advanced lung cancer (N = 248) were enrolled in a questionnaire survey conducted at 16 hospitals in Japan. Their priorities were assessed using a free-text response to the question what is the most important thing to you now? at the time of diagnosis and 3 months after diagnosis. The free-text responses were classified into 10 categories for quantification. The clinical characteristics associated with the category describing daily life were further examined. RESULTS: Free-text comments were obtained from 103 (44.0%) and 66 (42.6%) patients at the time of diagnosis and at 3 months, respectively. The most frequent categories were family (at diagnosis: 50.5%; at 3 months: 50.0%) and daily life (at diagnosis: 33.0%; at 3 months: 36.4%), followed by health (at diagnosis: 32.0%; at 3 months: 27.3%) at both time points. The patients mentioning daily life, the issues related to how to spend daily life, showed significantly higher total scores and functional well-being subscale scores on the Functional Assessment of Cancer Therapy-Lung scale at both time points and lower depression scores at diagnosis and lower anxiety scores at 3 months on the Hospital Anxiety and Depression Scale. CONCLUSION: Family and daily life were highly valued by patients with advanced lung cancer at diagnosis. A better quality of life and better mood were associated with mentioning daily life, which should be taken into account in care planning to maintain patients' involvement in daily life even with incurable diseases.